Metaprogramming Ruby 2 : program like the Ruby pros - Perrotta, Paolo (Facets of Ruby series., 2014)
Write powerful Ruby code that is easy to maintain and change. With metaprogramming, you can produce elegant, clean, and beautiful programs. Once the domain of expert Rubyists, metaprogramming is now accessible to programmers of all levels. This thoroughly revised and updated second edition of the bestselling Metaprogramming Ruby explains metaprogramming in a down-to-earth style and arms you with a practical toolbox that will help you write your best Ruby code ever.